Navigating Identity: The Lived Experiences Javanese Women with Polycystic Ovary Syndrome (PCOS) - Istiqomah, Neina Qonita; Candoruk, Agit (Faculty of Psychology, UIN Sunan Gunung Djati, Bandung Indonesia, 2025)
Polycystic Ovary Syndrome (PCOS) is a hormonal disorder in women of reproductive age, characterised by a constellation of symptoms including menstrual irregularities, hyperandrogenism and the presence of polycystic ovaries. In a culturally rich context such as Java, the experience of living with PCOS can be highly complex, with various cultural, social and personal factors interacting in a multitude of ways. This study explores how Javanese women with polycystic ovary syndrome (PCOS) navigate their identities within the sociocultural and religious context of Indonesia. A phenomenological approach was employed in the investigation, whereby in-depth interviews were conducted with ten Javanese women diagnosed with PCOS. Thematic analysis identified four key themes from the thematic analysis of the research data and were subsequently interpreted as a representation of the lived experiences of Javanese women with PCOS. he four identified themes are as follows: (1) thoughts about the illness, (2) percepetions of gender roles, (3) religious aspects and (4) social interactions.